2004
DOI: 10.1128/jcm.42.11.5429-5431.2004
|View full text |Cite
|
Sign up to set email alerts
|

Catheter-Related Bloodstream Infection Caused by Mycobacterium brumae

Abstract: Mycobacterium brumae is a rapidly growing environmental mycobacterial species identified in 1993; so far, no infections by this organism have been reported. Here we present a catheter-related M. brumae bloodstream infection in a 54-year-old woman with breast cancer. The patient presented with high fever (39.7°C), and >1,000 colonies of M. brumae grew from a quantitative culture of blood drawn through the catheter. A paired peripheral blood culture was negative, however, suggesting circulational control of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…Growth occurs within 5 days at 30°C and 37°C. In liquid medium, M. brumae forms clumps with cording morphology ( 2 ). The cell wall of M. brumae contains only α-mycolic acids, which only release docosanoate after pyrolysis ( 1 ).…”
Section: Genome Announcementmentioning
confidence: 99%
See 1 more Smart Citation
“…Growth occurs within 5 days at 30°C and 37°C. In liquid medium, M. brumae forms clumps with cording morphology ( 2 ). The cell wall of M. brumae contains only α-mycolic acids, which only release docosanoate after pyrolysis ( 1 ).…”
Section: Genome Announcementmentioning
confidence: 99%
“…Until now, no attention has been paid to this mycobacterium species, because no cases of infection due to M. brumae have been described in animals or humans. In 2004, Han et al reported a catheter-infection case related to this species ( 2 ), but it was later confirmed that the isolate strain was not M. brumae ( 3 ).…”
Section: Genome Announcementmentioning
confidence: 99%
“…The glycopeptide agents in clinical use are vancomycin and teicoplanin. Although there have been some reported successes with vancomycin as an antimycobacterial agent in humans and animals (150,176,208), mycobacteria are usually considered to be resistant to this agent. Although direct studies of the action of vancomycin in mycobacteria are lacking, indirect evidence for the peptidoglycan precursors present in mycobacteria following exposure to these agents suggests that the mechanism of action of vancomycin is the same as that in other bacteria (228).…”
Section: Inhibition Of Mycobacterial Cell Wall Synthesismentioning
confidence: 99%
“…Another newly described species, M. brumae, has also been the cause of catheter-related sepsis (208).…”
Section: Catheter Infections and Bacteremiamentioning
confidence: 99%
“…Rarely encountered species include Mycobacterium novocastrense, which is responsible for cutaneous infections (33); Mycobacterium hodleri, which causes opportunistic infections in the course of rheumatoid arthritis (40); Mycobacterium neoaurum, which was isolated from a patient with catheter-related bacteremia (46); Mycobacterium flavescens, which caused a disseminated infection in a probable case of chronic granulomatous disease (8); and Mycobacterium thermoresistible, which was responsible for an infection following kneereplacement surgery (20). Other species were isolated from human samples, such as Mycobacterium hassiacum from urine (32); Mycobacterium elephantis from the sputum and granulomatous tissue of an axillary lymph node (26,37,39); Mycobacterium doricum from cerebrospinal fluid (38); Mycobacterium brumae from sputum and a case of catheter-related bacteremia (21,22); Mycobacterium brisbanense from the antral sinus (31); Mycobacterium confluentis from sputum (17); Mycobacterium holsaticum from sputum, urine, and gastric fluid (28); Mycobacterium cosmeticum from a footbath drain and a granulomatous subdermal lesion in a female patient who was undergoing mesotherapy (12); and Mycobacterium canariasense from the blood of a patient with febrile syndrome (15).We report here on an additional novel RGM species isolated from respiratory specimens. …”
mentioning
confidence: 99%